Peculiarities of particles and field dynamics at critical intensity of electromagnetic waves (Part I) - Buts, V.A. (Вопросы атомной науки и техники, 2005)
Some results of study of the charged particles that are moving in a field of intensive electromagnetic waves are represented. The integrals are investigated and some schemes of laser acceleration are considered. It was revealed that the most effective scheme of acceleration is the scheme, in which the laser pulse with circular polarization is used. Is shown that the forces of radiating friction can promote transferring of energy from a laser field to particles. Besides is shown, that for laser acceleration the force of radiating friction are considerably less essential, than in cyclic accelerators.